58.1k views
5 votes
Solve for u.

-3(-6u+5) – 7u= 3 (u-4) - 1

Simplify your answer as much as possible.

User DACW
by
5.1k points

2 Answers

4 votes

Answer:

9

Explanation:

User Ianks
by
5.8k points
4 votes

Answer:

1/4

Explanation:

1. 18u−15−7u=3u−12−1

2. 11u−15=3u−12−1 (Simplify 18u-15-7u18u−15−7u to 11u-1511u−15)

3. 11u−15=3u−13 (Simplify 3u-12-13u−12−1 to 3u-133u−13)

4. 11u=3u−13+15 (Add 1515 to both sides)

5. 11u=3u+2 ( Simplify 3u-13+153u−13+15 to 3u+23u+2)

6. 11u−3u=2 ( Subtract 3u3u from both sides)

7. 8u=2 ( Simplify 11u-3u11u−3u to 8u)

8. u= 2/8 (Divide both sides by 8)

9.u=1/4 (Simplify 2/8 to 1/4)

User Gaberocksall
by
5.6k points